Sistem Informasi Persediaan Barang Dagang Berbasis Web Pada Toko Linnia Collection - Dieny Putri Nur Asyifa; Haris Ihsanil Huda; Eko Siswanto; Ahmad Ashifuddin Aqham; Dendy Kurniawan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to develop a web-based inventory information system to improve operational efficiency and data accuracy at Toko Linnia Collection. The research method used is Research and Development (R&D) with a prototyping approach. The system was developed using PHP programming language and MySQL database, and includes key features such as automated stock recording, PDF reporting, and multi-user role management. The implementation results show a 65% improvement in recording efficiency, a significant reduction in data entry errors, and easier system access for both the owner and employees. Based on blackbox testing, all system features function as expected. In conclusion, the system effectively addresses the real needs of inventory management in MSMEs and provides a practical and reliable solution for inventory digitalization.